2019
DOI: 10.1111/hir.12250
|View full text |Cite
|
Sign up to set email alerts
|

Health information in the digital age: an empirical study of the perceived benefits and costs of seeking and using health information from online sources

Abstract: Objective This paper aims to explore the determinants of the online health information seeking (OHIS) and usage (OHIU) behaviours of consumers based on the perceived benefits and costs of such activities. Methods This study applies questionnaires and empirical research methods. A questionnaire is designed according to the hypothesis model. A total of 282 questionnaires are obtained from patients and their accompanying families in two large hospitals, and the SPSS 17.0 and AMOS 17.0 (IBM, Almond, NY, USA) softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
0
17
0
3
Order By: Relevance
“…The perceived cost can be divided into cognitive costs and execution costs, referring to users' psychological, cognitive responses, or evaluation of online health information seeking and the time, materials, or other resources it takes [11]. Therefore, the conclusion that users' online health information seeking behavior is influenced by time, ability, and other factors is convincing, just as previous studies have suggested [1,11,36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The perceived cost can be divided into cognitive costs and execution costs, referring to users' psychological, cognitive responses, or evaluation of online health information seeking and the time, materials, or other resources it takes [11]. Therefore, the conclusion that users' online health information seeking behavior is influenced by time, ability, and other factors is convincing, just as previous studies have suggested [1,11,36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proposed that the effect of high Internet penetration rate and the accessibility of online health information reduce users' cognitive costs [1]. The resources users spend on OHISB for learning and using the technology is less than before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Internet, including social media, holds great potential in the communication of self-care and health-related information, and increasing numbers of people are using the Internet to seek such information (Lin, Zhang, Song, & Omori, 2016;Miller & Bell, 2012;Ren, Deng, Hong, & Zhang, 2019). Seeking and scanning health information is associated with gains in knowledge and implementing health behaviours (Shim, Kelly, & Hornik, 2006).…”
Section: Introductionmentioning
confidence: 99%